Technology Integration Trends in Hybrid Learning Environments in Indonesia: A Systematic Literature Review - Nugraha, Christophorus Ardi; Iskandar, Regina; Baeha, Putri Dwinatalis (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
This study aims to identify the most used technologies in face-to-face or hybrid learning environments in Indonesia and identify how these technologies are used. The collected data is processed using PRISMA Statement. The sorting process is conducted by three researchers collaboratively. The articles are then processed to know how the technology is used, what the brand is, what subjects, and the level of acceptance. From 121 selected articles, the following findings were obtained. Technology is most widely used for learning media (65). Most articles do not mention the brand(33). Most did not mention subjects (25). The acceptance of technology is positive (111). It can be concluded that technology tends to be used for learning and less to build a learning environment, professional development, or school administration. Technology is widely used for STEM lessons, Indonesian Language, and Islamic Religious Education and less for arts and social science subjects. Abstrak Penelitian ini bertujuan untuk mengidentifikasi teknologi yang paling sering digunakan di lingkungan belajar tatap muka atau hybrid di Indonesia dan mengidentifikasi bagaimana teknologi tersebut digunakan. Data yang terkumpul diproses menggunakan PRISMA Statement. Proses penyortiran dilakukan tiga peneliti secara kolaboratif. Artikel lalu diproses untuk memperoleh informasi bagaimana teknologi digunakan, apa mereknya, mata pelajaran apa, dan tingkat penerimaannya. Dari 121 artikel terpilih, diperoleh temuan sebagai berikut. Teknologi paling banyak digunakan untuk media pembelajaran (65). Sebagian besar artikel tidak menyebutkan merek teknologi yang digunakan (33). Sebagian besar tidak menyebutkan mata pelajaran (25). Sebagian besar penerimaan terhadap teknologi adalah positif (111). Dapat disimpulkan bahwa teknologi cenderung digunakan untuk pembelajaran dan kurang dimanfaatkan untuk membangun lingkungan belajar, pengembangan profesi, atau administrasi sekolah. Teknologi banyak digunakan untuk pelajaran STEM, Bahasa Indonesia, dan Pendidikan Agama Islam serta kurang dimanfaatkan untuk mata pelajaran seni dan ilmu pengetahuan sosial.